Golden girl - Hilderbrand, Elin (New York : Little Brown & Co., 2021)
A successful Nantucket novelist entering the afterlife due to a hit and run accident, learns she can observe the earthly lives of her nearly grown children for one final summer and is also permitted three "nudges" to alter the outcome of events.
Keywords: Women authors -- Death -- Fiction; Future life -- Fiction; Hit-and-run drivers -- Fiction; Mother and child -- Fiction; Secrecy -- Fiction; Hit-and-run drivers -- Fiction; Adult children -- Fiction; Nantucket (Mass.) -- Fiction; Large type books; Fantasy fiction; Psychological fiction